Dynamic hematological responses in endurance horses: unraveling blood physiological markers of exercise stress and recovery - de Siqueira, R. F.; Fernandes, W. R. (International Journal of Equine Science, 2024)
This study aimed to investigate the effects of endurance exercise on erythrogram parameters and identify stress and inflammation markers that could serve as reliable indicators for assessing recovery in endurance horses. The study involved 26 Arabian endurance horses (4 stallions and 22 geldings) aged between 8 and 12 years, each completing a race (10 horses in 80 km, 10 horses in 120 km, and 6 horses in 160 km). Blood samples were collected at six different time points: at rest (T0), immediately after the race (T1), 3 hours after the race (T2), and 3, 7, and 14 days after the race (T3, T4, T5). The hemogram analyses included several hematological indices such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), eosinophil-to-lymphocyte ratio (ELR), red blood cell distribution width-to-platelet ratio (RDW/PLT), hemoglobin-to-red blood cell distribution width ratio (Hb/RDW), hemoglobin-to-platelet ratio (Hb/PLT), systemic inflammation index (SII), systemic inflammatory response index (SIRI), leukocyte shift index (LSI), and adaptation intensity index of L. Harkavy (AI). The findings revealed that some indices, such as NLR, PLR, SII, SIRI, MLR, RDW/PLT, and LSI, were sensitive to acute physiological changes related to the endurance race. These indices showed significant variations immediately after the race, indicating a stress and inflammatory response. In contrast, the ELR and AI indices displayed delayed and more prolonged responses, suggesting their utility in monitoring the post-exercise recovery phase. Overall, this study offers insights into applying hematological markers to assess endurance horses' stress, inflammation, and recovery. These findings could contribute to improved training and recovery strategies, promoting the health and welfare of equine athletes during and after intense physical exertion. Further research is recommended to explore these indices in larger samples and other equine sports.